Endovascular Perfusion Augmentation for Critical Care Decreases Vasopressor Requirements while Maintaining Renal Perfusion. Issue 5 (May 2022) - Patel, Nathan T.P.; Gaffley, Michaela; Leblanc, Mathias J.R.; Lane, Magan R.; Kratky, Lauren E.; Hoareau, Guillaume L.; Johnson, M. Austin; Jordan, James E.; Neff, Lucas P.; Williams, Timothy K.
ABSTRACT: Background: Ischemia reperfusion injury causes a profound hyperdynamic distributive shock. Endovascular perfusion augmentation for critical care (EPACC) has emerged as a hemodynamic adjunct to vasopressors and crystalloid. The objective of this study was to examine varying levels of mechanical support for the treatment of ischemiareperfusion injury in swine. Methods: Fifteen swine underwent anesthesia and then a controlled 30% blood volume hemorrhage followed by 30 min of supra-celiac aortic occlusion to create an ischemia-reperfusion injury Animals were randomized to standardized critical care (SCC), EPACC with low threshold (EPACC-Low), and EPACC with high threshold (EPACC-High). The intervention phase lasted 270 min after injury Hemodynamic markers and laboratory values of ischemia were recorded. Results: During the intervention phase, SCC spent 82.4% of the time avoiding proximal hypotension (>60 mm Hg), while EPACC-Low spent 97.6% and EPACC-High spent 99.5% of the time avoiding proximal hypotension, P < 0.001. Renal artery flow was statistically increased in EPACC-Low compared with SCC (2.29 mL/min/kg vs. 1.77 mL/ min/kg, P < 0.001), while renal flow for EPACC-High was statistically decreased compared with SCC (1.25 mL/min/kg vs. 1.77 mL/min/kg, P < 0.001). EPACC animals required less intravenous norepinephrine, (EPACC-Low: 16.23mcg/kg and EPACC-High: 13.72 mcg/kg), compared with SCC (59.45 mcg/kg), P = 0.049 and P = 0.013 respectively. Conclusions: Compared with SCC, EPACC-High and EPACC-Low had decreased norepinephrine requirements with decreased frequency of proximal hypotension. EPACC-Low paradoxically had increased renal perfusion despite having a mechanical resistor in the aorta proximal to the renal arteries. This is the first description of low volume mechanical hemodynamic support in the setting of profound shock from ischemia-reperfusion injury in swine demonstrating stabilized proximal hemodynamics and augmented distal perfusion.